[PP.08.30] DIABETES MELLITUS IN HYPERTENSIVE PATIENT - SYNONYM OF CARDIOVASCULAR RISK INCREASE?. (September 2017) - Freixa, M.; Simões, A. Ferreira; Rodrigues, J.; Úria, S.; Silva, G.
Abstract : Objective: Hypertension (HT) is an independent cardiovascular risk factor (CVRF), but the association with diabetes mellitus (DM) may lead to increased cardiovascular morbidity and mortality. The authors sought to study the association between HT and DM in hospitalized patients. Design and method: Retrospective study of 1106 patients admitted to an Internal Medicine ward between January 2012 and November 2016. Patients with HT were selected and grouped according to the presence of DM: G1 - diabetic hypertensive patients; G2 - non-diabetic hypertensive patients. We defined cardiovascular events (CVE): acute myocardial infarction (AMI) and stroke, reasons for hospitalization; and considered in-hospital mortality of all causes. Results: (1) 758 patients (68.5% of the population) were included. (2) In G1 the mean age was lower (77.7 ± 9.8 vs 79.8 ± 11.8 years, p = 0.014) and the hospital length of stay was higher (11.2 ± 10.9 vs 9.9 ± 8.5 days; p = 0.075). (3) In G1 there was a higher prevalence of heart failure (38.7vs28.5%, p = 0.004) and ischemic heart disease (19.2vs11.6%, p = 0.004), cerebrovascular disease (14.3vs21.3%; p = 0.018), being similar in chronic kidney disease (32.8vs31.5%, p = 0.816) and atrial fibrillation (25.9vs24.8%, p = 0.729). (4) There is a greater association with other CVRF in G1: obesity (16.2vs7.3%, p < 0.01) and dyslipidemia (51.9vs33.5%, p < 0.01). (5) There were no differences in CVE (4.5vs5.9%, p = 0.422, AMI 3.0vs2.4%, p = 0.641, stroke 4.5vs6.7%, p = 0.222), mortality (2, 6vs4.5%, p = 0, 208) and in the combined CVD and mortality (10.2vs12.4%, p = 0.356). Conclusions: In this sample, the presence of DM did not confer disadvantage in hypertensive patients contrary to expectations. This may be due to a earlier and rigorous control of CVRF, in particular of hypertension, in the diabetic patient, with more effective therapeutic strategies, which cooperate for a greater prevention of CVD and better cardiovascular outcome.